BMP/TGF‐β signaling as a modulator of neurodegeneration in ALS. Issue 1 (29th March 2021) - Russo, Kathryn; Wharton, Kristi A.
Abstract: This commentary focuses on the emerging intersection between BMP/TGF‐β signaling roles in nervous system function and the amyotrophic lateral sclerosis (ALS) disease state. Future research is critical to elucidate the molecular underpinnings of this intersection of the cellular processes disrupted in ALS and those influenced by BMP/TGF‐β signaling, including synapse structure, neurotransmission, plasticity, and neuroinflammation. Such knowledge promises to inform us of ideal entry points for the targeted modulation of dysfunctional cellular processes in an effort to abrogate ALS pathologies. It is likely that different interventions are required, either at discrete points in disease progression, or across multiple dysfunctional processes which together lead to motor neuron degeneration and death. We discuss the challenging, but intriguing idea that modulation of the pleiotropic nature of BMP/TGF‐β signaling could be advantageous, as a way to simultaneously treat defects in more than one cell process across different forms of ALS. Key Findings: Gene mutations and environmental triggers of ALS primarily perturb protein homeostasis, RNA function, and cytoskeletal dynamics. Emerging data reveal specific molecular links between BMP/TGF‐β signaling and dysfunctional cellular processes in ALS. The pleiotropic nature of BMP/TGF‐β signaling may prove advantageous as a pathway whose modulation will impact multiple processes simultaneously versus the need to develop multiple interventions to slow or prevent motor decline in ALS.